Impact of Economic Currency Counterfeiting in Germany in World War II (1939-1945) - Anantha Andhikatama Dalimunthe; Guntur Eko Saputro; Lukman Yudho Prakoso (Faculty of teaching training and education, 2023)
In World War II one of the German strategies was the counterfeiting of currency to be used to purchase goods or services. Therefore, it is important to understand the background and consequences of currency counterfeiting in World War II. As a strategy used to weaken a country's economy, as well as the consequences of counterfeiting the currency using several stages including the heuristic stage, namely the stage of collecting primary data sources in the form of archives, news, newspapers, and secondary data in the form of books, articles then verifying or historical criticism, efforts to assess compatibility with events during the period (1939-1945) then interpretation (interpretation) so that the writing is objective data taken from several countries involved in World War II, then writing is done as a whole and analyzing in time order. Some of the impacts arising from the counterfeiting of currency by Germany are as follows: Inflation and economic instability, Harm to civil society, Financial loss to other countries. Germany also received severe political and economic sanctions at the end of World War II for counterfeiting currency and engaging in economic practices that harmed other countries. Sanctions were imposed on Germany at that time. With historical research conducted by heuristics, verification of historical criticism, interpretation, and historiography, we can better understand the counterfeiting of currency in World War II and its relevance for the present.